1991
DOI: 10.1159/000235413
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of the Epitope Locations of Human Autoanti-IgE: Recognition of Two Epitopes Located within the Cε2 and the Cε4 Domains

Abstract: IgG autoanti-IgE is detectable in a large proportion of individuals with allergic asthma, where it is suggested to be potentially involved in modulating IgE-mediated hypersensitivity. Using a series of overlapping recombinant human ε-chain peptides, we have shown that circulating IgG anti-IgE antibodies recognise at least 2 epitopes located within the Cε2 and the Cε4 domains, respectively. The Cε2 recognition site is located within the C-terminal portion of the Cε2 domain (i.e. aa301–339) which is thought to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
24
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 11 publications
5
24
0
Order By: Relevance
“…IgG anti-IgE autoantibodies are a heterogeneous population of antibodies that execute functions of physiological control of the specific IgE Th2 immune response, as inhibition of IgE synthesis and removal of IgE from CD23 receptor (Stadler et al 1993b). In atopic diseases as asthma these autoantibodies have been implicated in the modulation of the IgE immune response, mainly because they may react with epitopes located in C epsilon 2 domain of IgE, which is involved in the binding of this immunoglobulin on Fcε high affinity receptor (FcεRI) on the surface of basophils and mast cells, preventing the sensitization of these cells (Shakib & Powell-Richards 1991, Stadler et al 1995.…”
Section: Discussionmentioning
confidence: 99%
“…IgG anti-IgE autoantibodies are a heterogeneous population of antibodies that execute functions of physiological control of the specific IgE Th2 immune response, as inhibition of IgE synthesis and removal of IgE from CD23 receptor (Stadler et al 1993b). In atopic diseases as asthma these autoantibodies have been implicated in the modulation of the IgE immune response, mainly because they may react with epitopes located in C epsilon 2 domain of IgE, which is involved in the binding of this immunoglobulin on Fcε high affinity receptor (FcεRI) on the surface of basophils and mast cells, preventing the sensitization of these cells (Shakib & Powell-Richards 1991, Stadler et al 1995.…”
Section: Discussionmentioning
confidence: 99%
“…The specificity of the present ELISA has previously 244 Shakib/Mills/Powell-Richards Complexed IgG Subclass Anti-IgE been established by showing that the anti-rFce activity in the sera to be tested can be inhibited, in a concentrationdependent manner, by pre-incubation with rFce or native IgE, but not with similar concentrations of IgG, IgM or light chain protein [4], We have established that the increase in the IgG sub class anti-rFce activity of heated (30 min at 56°C) sera (see further below) is a specific phenomenon; since none of the sera tested showed a parallel increase in the IgG subclass anti-ovalbumin activity (table 1). It was further established that heating the serum samples (30 min at 56°C) destroys most of their IgE content (table 2) and, therefore, effect maximum release of anti-IgE.…”
Section: Resultsmentioning
confidence: 96%
“…We have recently shown, us ing a series of overlapping recombinant human e-chain peptides, that IgG anti-IgE antibodies recognize at least two autoantigenic epitopes located within the Ce2 (i.e. aa301-339) and the Ce4 domains respectively [4], The Ce2 epitope is particularly important, since it is located within the Ce2-Ce3 interdomain region [4], which contains the binding site for the high-affinity receptor (FceRI) on mast cells and basophils [5], In terms of subclass distribution the anti-IgE activity is mainly found in IgGl [2,6], which nor mally constitutes about 70% of total IgG in serum [7]. The subclass nature of IgG anti-IgE is of potential pathological relevance since IgG subclasses exhibit considerable var iation in their molecular configurations and effector func tions [8],…”
Section: Introductionmentioning
confidence: 99%
“…using purified IgE or isolated myeloma IgE coated to a solid phase [2,9]. Previous workers have indubitably demonstrated that the IgG autoantibody is directed against IgE epitope{s) residing within the Cf2 and the Cf4 domains of the 7E molecule [15]. Using 7G proteins of difFerent provenanee we have been able to detect-within the sensitivity limits of the assay system employed-only negligible traces of rheumatoid factor-like IgE anti-lgG autoantibodies in the sera of allergic individuals [16].…”
Section: Discussionmentioning
confidence: 99%